Is Loyalty Still the Same? An Investigation of the Antecedents of Loyalty - Sousa, Eduardo Mesquita de; Lopes, Evandro Luiz; Herrero, Eliane; Varotto, Luis Fernando (International Journal of Business, Economics and Management, 2020)
In this study we aimed to investigate the effects of satisfaction, perceived value and value for money on the relationship between store attributes and loyalty. This research is based on an Indian study that presents controversial results on the theory of marketing, namely: value for money has a low and negative impact on loyalty and sales promotion does not influence the customer’s perception of value for money. This theory inspired our study which inserts two additional variables to the Indian model, for a better understanding of the results. The aim of this study was to investigate the background of consumer loyalty in conjunction with value for money, perceived value and retail satisfaction, in an emerging country: Brazil. To achieve the objective, a survey was conducted, answered by 516 retail customers in the city of São Paulo and the data were analyzed using Structural Equation Modeling (SEM). The results show that value for money, as well as satisfaction and perceived value, impacts loyalty. It was also found that all the retail attributes tested in this research contribute, in some way, to establishing loyalty of retail customers, even in a retail context of an emerging market (Brazil).